2019
DOI: 10.30935/cet.590099
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Teachers’ Pedagogical Use of ICT in Secondary Schools: A Case of Ghana

Abstract: Technology is perceived as a vital driving force for contemporary education. The Government of Ghana acknowledges the relevance of Information and Communication Technology (ICT) in education, and it is financing ICT in secondary schools. However, most instructors are unwilling to integrate ICT into their teaching. Therefore, the purpose of this study was to investigate the factors that influence secondary school teachers' ICT usage in schools. The participants were 376 teachers randomly selected from 24 public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
5
19
0
Order By: Relevance
“…Technological pedagogical content knowledge (TPACK) is a useful ICT integration model in education proposed by [54][55]. The model built on [55] Awareness of the Pedagogical Material (PCK) requires technical knowledge as part of technological teaching. Some research found this to be one of the critical factors that affect ICT success in education [56][57] [58][59][60] [61].…”
Section: Digital Literacy Decreases the Cognitive Load Of Working Memory When Studying Chemistrymentioning
confidence: 99%
“…Technological pedagogical content knowledge (TPACK) is a useful ICT integration model in education proposed by [54][55]. The model built on [55] Awareness of the Pedagogical Material (PCK) requires technical knowledge as part of technological teaching. Some research found this to be one of the critical factors that affect ICT success in education [56][57] [58][59][60] [61].…”
Section: Digital Literacy Decreases the Cognitive Load Of Working Memory When Studying Chemistrymentioning
confidence: 99%
“…The staffs are as important for the success of the technology plan as hardware and software, and professionals with great skills, and those with an awareness of how technology fits with instruction. The lack of technical assistance has decreased educators from implementing their teachings by means of ICT (Buabeng‐Andoh, 2019). According to Basak and Govender (2015), lack of technical support means no aid waiting for websites to be accessed, the Internet cannot be connected, printers do not print, machine malfunctioning is not available; administrative support is not available; teachers who use technology are not assisted in‐site; student monitoring is insufficient when using device.. All of the previous issues will affect the positive adoption and application of ICT in teaching and learning by the students. Availability of Time …”
Section: Methodsmentioning
confidence: 99%
“…For example, Koen et al (2017) show that there are persistent and growing differences in data infrastructure between urban and rural areas and, if we view urban areas as having higher socioeconomic status, this is an indirect, positive correlation with the availability of ICT resources ( Yang et al, 2019 ). Furthermore, given that teachers in urban schools have been found to use ICT more frequently than those in semi-urban schools ( Buabeng-Andoh, 2019 ), perhaps we can assume that the frequency is higher than in rural areas as well. According to the same study, urban school teachers receive more training and leadership support than those in semi-urban schools ( Buabeng-Andoh, 2019 ), and, again, perhaps we can expect that it is also more than rural school teachers receive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, given that teachers in urban schools have been found to use ICT more frequently than those in semi-urban schools ( Buabeng-Andoh, 2019 ), perhaps we can assume that the frequency is higher than in rural areas as well. According to the same study, urban school teachers receive more training and leadership support than those in semi-urban schools ( Buabeng-Andoh, 2019 ), and, again, perhaps we can expect that it is also more than rural school teachers receive. Hamzah et al (2021) ’s results about the effects of principals’ digital leadership on teachers’ digital teaching during the COVID-19 pandemic in Malaysia indicate that the level of digital leadership displayed by principals and teachers’ digital teaching practice are in a positive correlation and that the ability to plan and organize digital leadership programs is important and can help improve Students’ academic performance, despite the COVID-19 pandemic crisis ( Karakose et al, 2021a ).…”
Section: Literature Reviewmentioning
confidence: 99%